Environmental Impacts Caused by Tidal Power Extraction in the Upper Bay of Fundy. Issue 3 (26th May 2016) - Wu, Yongsheng; Chaffey, Jason; Greenberg, David A.; Smith, Peter C.
ABSTRACT: Environmental impacts, including tidal regimes and sediment transport in the Minas Basin, caused by tidal power extraction in the Minas Passage have been investigated using a three-dimensional hydrodynamic model in which tidal power extraction is represented using an arbitrary method that adds a friction term to the standard momentum equations. Using the model results, changes in tidal processes and sediment transport in the Minas Basin are examined by comparing model results with and without power extraction. With the presence of power extraction, the tidal level decreases by 0.5–1.5% and the tidal phase increases by 1.2–1.8°. Tidal currents decrease by 15–35% at the western head of the Minas Basin and increase by a comparable magnitude at the Southern Bight. The presence of power extraction could move the location of the tidal residual gyre in the western head of the Minas Basin south by about 2 km. Model results also show that less sediment would move into the central area of the Minas Basin but more sediment would be deposited into the Southern Bight at a rate of 8–12 mm y −1 . The effect of the deposition rate might be negligible in the northern part of the Bight where the water is deep but could be important in the intertidal areas.